Vampires, Demons and the Disappearing Shadow in Folkloric Fictions of the Long Nineteenth Century. Issue 1 (March 2020) - George, Sam
Abstract : This article interrogates manifestations of the shadow soul, combining anthropological, magical and religious approaches to the shadow in an analysis of a small group of interrelated Gothic texts. It enters the shadowy worlds of Peter Schlemihl, protagonist of Hans Andersen's 'The Shadow', Dracula, and Peter Pan, who, on being detached from their shadows, have themselves become shades. This journey into the kingdom of shadows will uncover the folkloric demon, the vampire, the physiognomist, the satyr, the pagan Pan, and the Devil himself. To read these narratives through Frazer's The Golden Bough challenges conventional psychoanalytic readings and offers an alternative, folkloric perspective, one which lays bare the ritualistic and magical beliefs that inform late nineteenth- and early twentieth-century Gothic.